QUANTITATIVE ANALYSIS OF POTENTIAL CURRENCY CRISIS IN THE REPUBLIC OF SERBIA - Rađenović, Žarko; Kostić, Zorana Z (International Journal of Economic Practice and Policy, 2016)
The subject of this paper is theoretical and empirical analysis of potential currency crisis in the Republic of Serbia. The main aim of the paper is quantitative analysis of a set of key indicators (index of exchange market pressure, signal-to-noise ratio, misery index, a measure of openness and the monetary measure of openness of the country) that indicate the possibility of a currency crisis. The cyclic character of currency and financial crisis is forcing policymakers to conduct thoughtful exchange rate policy.  The aim of this is to prevent the scenario with which the countries of Latin America faced  in the late 20th century. Although there is no a significant correlation in terms of international trade transactions between Serbia and the countries of Latin America, we should certainly learn from the experience of these countries. It is necessary to continuously monitor the value of indicators which point to possible distortion. In the paper we use some econometric and statistical tools, such as correlation and regression analysis, to point to the values of indicators which can contribute to early detection of a currency crisis.
Keywords: the currency crisis; foreign exchange market; the Republic of Serbia; exogenous shocks